Dilemas modernos. el proyecto urbano en Montevideo y la costa balnearia - Articardi, Juan (Colección "Biblioteca plural" de la Universidad de la República., 2016)
Analysis of the the incorporation of the ideas of modern urbanism in Uruguay, particularly in the city of Montevideo in the first half of the 20th century, including Le Corbusier's, Plan for Montevideoʺ and its consequent progress and obstacles. The edition also explores the celebration of the futureʺ in which the Plan for the Centenary of Montevideo was developed, a territorial expansion that included the design of strategies for the urbanization of coastal areas which characterize and define the promenade of Montevideo and the whole set of projects of modern resorts.